Gene therapy and immunotherapy as promising strategies to combat Huntington's disease-associated neurodegeneration: emphasis on recent updates and future perspectives. (1st November 2020) - Jamwal, Sumit; Elsworth, John D; Rahi, Vikrant; Kumar, Puneet
ABSTRACT: Introduction: Modulation of gene expression using gene therapy as well as modulation of immune activation using immunotherapy has attracted considerable attention as rapidly emerging potential therapeutic intervention for the treatment of HD. Several preclinical and clinical trials for gene-based therapy and immunotherapy/antibody-based have been conducted. Areas covered: This review focused on the potential use of gene therapy and immuno-based therapies to treat HD, including the current status, the rationale for these approaches as well as preclinical and clinical data supporting it. Growing knowledge of HD pathogenesis has resulted in the discovery of new therapeutic targets, some of which are now in clinical trials. Focus has been allocated to RNA and DNA-based gene therapies for the reduction of mutant huntingtin (mHTT), using Immuno/antibody-based therapies. Expert opinion: While safety and efficacy of gene therapy and immunotherapy has been well demonstrated for HD, therefore much focus has now been shifted to disease-modifying therapies. This review defines the current status and future directions of gene therapy and immunotherapies. The review summarizes by what means HD genetic root cause modification and functional restoration of mHtt protein could be achieved by using targeted multimodality gene therapy and immunotherapy to target intracellular and extracellular mHtt.